ANALISIS SISTEMATIS PENERAPAN MANAJEMEN RISIKO TERINTEGRASI PADA PRODUK GARANSI BANK DI INDONESIA: PENDEKATAN SLR - Rendi Apriandi; Muhammad Zilal Hamzah (Media Ekonomi, 2025)
This study aims to analyze the implementation of integrated risk management in Bank Guarantee (GB) products in Indonesia within the banking sector using a Systematic Literature Review (SLR) approach based on PRISMA 2020. This study employs a qualitative SLR method using PRISMA 2020 guidelines. Data were collected from Scopus, Web of Science, and Google Scholar databases, yielding 340 identified articles, of which 25 met the inclusion criteria. The analysis was conducted using thematic analysis to identify patterns in the relationship between ERM, GCG, and GB risk management. The findings indicate that the implementation of ERM effectively identifies and controls multidimensional risks in GB products, while Good Corporate Governance strengthens ERM effectiveness through improved transparency, accountability, and oversight. The integration of ERM and GCG is associated with more stable guarantee volumes and lower claim ratios, contributing to adaptive and sustainable banking risk management systems. This study contributes to the literature by specifically examining the integration of ERM and GCG in the context of Bank Guarantee products, which remains underexplored in the existing literature.